THE EMERGENCE AND EVOLUTION OF APPROACHES TO THE CATEGORY OF "ECONOMIC SECURITY OF THE STATE" - Karimov Javlon Ko‘ziyevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article analyzes the emergence and evolution of approaches to the concept of "state economic security." The research examines historical stages in the development of the concept of economic security, tracking changes in scholarly views and its conceptual reinterpretation in alignment with contemporary economic conditions. The study thoroughly investigates the economic and political factors contributing to the formation of economic security as a concept, clearly distinguishing scientifically substantiated stages of its evolution.